2012
DOI: 10.1007/s11596-012-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein a polymorphism is associated with susceptibility to chronic obstructive pulmonary disease in Chinese Uighur population

Abstract: This study investigated the correlation between surfactant protein-A (SP-A) polymorphism and the susceptibility of chronic obstructive pulmonary disease (COPD) in Xinjiang Uighurs. Genomic DNA was extracted from peripheral blood of 194 COPD smokers and 201 healthy smokers of Uighur who were hospitalized in or paid a visit to one of the four Xinjiang-based hospitals involved in the study, from March 2009 to December 2010. Single nucleotide polymorphisms (SNPs) were studied at aa62 (CCA/CCG rs1136451) and aa219 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Other studies have found rs1059057 to be associated with acute lung injury 22 and cystic fibrosis, 44 and rs1136451 with susceptibility to chronic obstructive pulmonary disease (COPD) and analysed gene–environment effects from tobacco smoking. 24 The SP-A 2 SNP rs4253527 has been associated with tuberculosis. 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found rs1059057 to be associated with acute lung injury 22 and cystic fibrosis, 44 and rs1136451 with susceptibility to chronic obstructive pulmonary disease (COPD) and analysed gene–environment effects from tobacco smoking. 24 The SP-A 2 SNP rs4253527 has been associated with tuberculosis. 22 …”
Section: Discussionmentioning
confidence: 99%
“…22 SNPs in SP-A coding regions have been associated with multiple respiratory diseases, 14 23 as well as gene-environment interactions for smoking and chronic obstructive pulmonary disease. 24 Many questions remain as to what components of air pollution are harmful in a general population, in particular at relatively low pollution exposures, and if such associations are modified by genetic factors. Thus, the aim of the current study was to investigate the effects of different PM sources determined from a state-of-the-art dispersion model on lung function in a general population cohort, and to investigate lung function effects of genotype and gene-environment interaction with particle exposures types.…”
Section: Strength and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…5,11 In recent years, the pathogenesis of genetic susceptibility in COPD has been increasingly studied. [12][13][14] The a-antitrypsin gene was the first to be investigated and was recognized as a COPDincidence-correlated gene. 15 The a-antitrypsin gene has multiple polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a minority of smokers (10–20%) suffer from COPD, indicating that in addition to smoking, there are other factors involve 5,11 . In recent years, the pathogenesis of genetic susceptibility in COPD has been increasingly studied 12–14 . The α‐antitrypsin gene was the first to be investigated and was recognized as a COPD‐incidence‐correlated gene 15 .…”
Section: Discussionmentioning
confidence: 99%